Constrictive Pericarditis with a Calcific Mass Invading into the Right Ventricular Myocardium. Issue 1 (28th November 2012) - Ahlgren, Bryan; Reece, Brett; Salcedo, Ernesto; Seres, Tamas
<x xml:space="preserve">Abstract</x> We present a rare and unique case of calcific constrictive pericarditis with a calcified pericardial mass invading the right ventricular myocardium. Perioperative two‐dimensional and three‐dimensional transesophageal echocardiography revealed the extent and structure of the pericardial mass and led to the repair of the right ventricular free wall as a surgical intervention.